2021
DOI: 10.1167/iovs.62.10.11
|View full text |Cite
|
Sign up to set email alerts
|

Meridional Anisotropy of Foveal and Peripheral Resolution Acuity in Adults With Emmetropia, Myopia, and Astigmatism

Abstract: Purpose To quantify astigmatism-related meridional anisotropy in visual resolution at central, nasal, and inferior visual fields. Methods Three groups of young adults (range, 18–30 years) with corrected-to-normal visual acuity (logMAR 0) were recruited: (1) myopic astigmats (MA): spherical-equivalent error (SE) < −0.75D, with-the-rule astigmatism ≥ 2.00D, n = 19; (2) simple myopes (SM): SE < −0.75D, astigmatism ≤ 0.50D, n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Moreover, studies involving animal models have demonstrated that the peripheral retina refraction status dominated refractive changes whenever conflicts occur between the fovea and the peripheral visual signals ( 6 ). Therefore, this finding calls for the measurement of both the central and relative peripheral refractive errors with the overarching goal of elucidating the mechanisms of myopic development ( 7 ). It has been reported that inhibiting the progression of myopia by reducing the hyperopic defocus of the peripheral retina following a refractive correction is an effective method ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies involving animal models have demonstrated that the peripheral retina refraction status dominated refractive changes whenever conflicts occur between the fovea and the peripheral visual signals ( 6 ). Therefore, this finding calls for the measurement of both the central and relative peripheral refractive errors with the overarching goal of elucidating the mechanisms of myopic development ( 7 ). It has been reported that inhibiting the progression of myopia by reducing the hyperopic defocus of the peripheral retina following a refractive correction is an effective method ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…This confirmed the inversion of the horizontal-vertical foveal asymmetry found in myopic WTR astigmatism. 46 …”
Section: Resultsmentioning
confidence: 99%
“…This confirmed the inversion of the horizontal-vertical foveal asymmetry found in myopic WTR astigmatism. 46 RA: Horizontal and vertical also showed significant differences in resolution acuity in meridional difference (|V − H| = 6.703 ± 0.486, one sample t(8) = 13.794, p < 0.001), but, in contrast with RTs, the direction of fVHA varied among subjects. fVHA and Refractive Errors RA: When subjects attended target orientation, the vertical-horizontal asymmetry increased in line with the amount of defocus (Figure 3A, fVHA V congruent /H congruent Sph: r(9) = 0.711, p = 0.032; Cyl: r(9) = −0.253, p = 0.512), such that higher myopes had better vertical acuity than lower myopes.…”
Section: Fvhamentioning
confidence: 88%
See 2 more Smart Citations